THE RELATIONSHIP BETWEEN SCREEN TIME AND NUTRITIONAL STATUS IN STUDENTS OF THE FACULTY OF MEDICINE, MUSLIM UNIVERSITY OF INDONESIA CLASS OF 2021 - M., Andi Nurdina; Nurmadilla, Nesyana; Novriansyah, Zulfikri Khalil; Namirah, Hanna Aulia; Safitri, Asrini (HEARTY, 2025)
Screen time refers to the duration a person spends looking at electronic device screens, such as cell phones, computers, tablets, or televisions. High screen time can influence various aspects of life, including energy intake, physical activity, and nutritional status. This study aims to explore the relationship between screen time and nutritional status among students of the Faculty of Medicine, Muslim University of Indonesia (UMI) class of 2021. Using an observational cross-sectional design, the study involved students as respondents. Results indicated that 51% of students had sufficient screen time, while 49% had normal nutritional status. Data analysis using the chi-square test yielded a p-value of 0.118, suggesting no significant relationship between screen time and nutritional status (p > 0.05). Although screen time is often linked to lifestyle changes, such as reduced physical activity or unhealthy eating, this study concludes that it does not directly impact nutritional status in this population. The findings may serve as a foundation for future research that considers additional factors influencing nutritional status.